KESEPIAN DAN SELF COMPASSION MAHASISWA PERANTAU - Dinda Marisa; Nelia Afriyeni (Psibernetika, 2019)
This research aimed to see the correlation between self compassion with loneliness in overseas students of Andalas University. The research method used in this study was quantitative method. The UCLA Loneliness Scale (Version 3) and Neff Self-Compassion Scale was used as measuring instrument in this research. The subjects in this research amounted to 100 people who were obtained using accidental sampling technique. The data was analyzed using Pearson Product Moment correlation analysis. The result of the correlation analysis showed that there was a significant negative relationship at the moderate level between self compassion and loneliness in overseas students of Andalas University (r=-0,538; p=0,000). It means that the higher the self compassion possessed by overseas students of Andalas University, the loneliness that they feel will be lower. The calculation of hypothetical scores indicate that perceived loneliness and self-compassion possessed by the overseas students of Andalas University were in the moderate category. In terms of gender, there was no difference in loneliness felt by male and female overseas students of Andalas University. ABSTRACT: This research aimed to see the correlation between self compassion with loneliness in overseas students of Andalas University. The research method used in this study was quantitative method. The UCLA Loneliness Scale (Version 3) and Neff Self-Compassion Scale was used as measuring instrument in this research. The subjects in this research amounted to 100 people who were obtained using accidental sampling technique. The data was analyzed using Pearson Product Moment correlation analysis. The result of the correlation analysis showed that there was a significant negative relationship at the moderate level between self compassion and loneliness in overseas students of Andalas University (r=-0,538; p=0,000). It means that the higher the self compassion possessed by overseas students of Andalas University, the loneliness that they feel will be lower. The calculation of hypothetical scores indicate that perceived loneliness and self-compassion possessed by the overseas students of Andalas University were in the moderate category. In terms of gender, there was no difference in loneliness felt by male and female overseas students of Andalas University.Keywords: Loneliness, Overseas Students, Self-Compassion ABSTRAK: Penelitian ini bertujuan untuk mengetahui hubungan antara self compassion dengan kesepian pada mahasiswa perantau Universitas Andalas. Metode penelitian yang digunakan adalah metode kuantitatif. UCLA Loneliness Scale (Version 3) dan Neff Self-Compassion Scale digunakan sebagai alat ukur dalam penelitian ini. Subjek penelitian berjumlah 100 orang yang didapatkan menggunakan teknik accidental sampling. Pengolahan data dilakukan menggunakan analisis korelasi Pearson Product Moment. Hasil analisis korelasi menunjukkan bahwa terdapat hubungan negatif yang signifikan pada taraf sedang antara self compassion dengan kesepian pada mahasiswa perantau Universitas Andalas (r=-0,538; p=0,000). Artinya, semakin tinggi self compassion yang dimiliki oleh mahasiswa perantau Universitas Andalas, kesepian yang dirasakan akan semakin rendah. Hasil perhitungan skor hipotetik menunjukkan bahwa kesepian yang dirasakan dan self compassion yang dimiliki oleh mahasiswa perantau Universitas Andalas berada pada kategori sedang. Jika dilihat dari jenis kelamin, tidak terdapat perbedaan kesepian yang dirasakan oleh mahasiswa perantau Universitas Andalas yang berjenis kelamin laki-laki dan perempuan.Kata Kunci: Kesepian, Mahasiswa Perantau, Self Compassion